Progrès technologique et structure industrielle régionale (un résumé de la littérature récente) - Martin, Fernand (L'Actualité économique)

(untitled) (HEC Montréal, 1982)
AbstractTechnological progress has two main regional implications: (a) to create employment out of technological progress, local generation of innovations is not essential; all that counts is access to innovation. Consequently, the relationship between local R. & D. and regional economic performance (measured by jobs created) is very variable. At worst, local R. & D. can profit mainly other regions of the country. (b) Because of the workings of the product cycle, peripheral regions inherit periodically decentralizable portions of high technology industries which can use cheap non-specialized labour; they also inherit matured industries (which have reached a low level of technology). Ceterisparibus, initially, the workings of the product cycle tend not to favour these regions in terms of technology.